A molding process for embedding a flexible FPC communication line in a special-shaped housing
Patent Information
- Application Number
- CN202610859149.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]针对现有技术的不足,本发明提供了一种柔性FPC通信线路在异形壳体中嵌入的成型工艺,解决了现有FPC嵌入注塑工艺中存在的聚酰亚胺基材弹性回弹导致定位偏差、异质材料界面结合力弱以及成型内应力过大引发翘曲与线路损伤的问题
[0035]1、本发明通过在预成型阶段实施高温蠕变与急冷定型工艺,有效解决了高刚性聚酰亚胺基材在异形曲面贴合时的弹性回弹问题。利用180℃至210℃的温度场促使基材分子链段发生应力松弛,将可逆的弹性形变转化为不可逆的粘塑性形变,并利用急冷工艺将材料状态快速固定,从而保证了预成型FPC与注塑模具型腔的精确贴合,提高了后续注塑成型的定位精度,避免了因FPC回弹导致的压伤或缺胶缺陷。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of injection molding technology, specifically to a molding process for embedding flexible FPC communication lines in irregularly shaped housings. Background Technology
[0002] As mobile communication terminals evolve towards thinner, lighter designs and more complex curved surfaces, directly embedding flexible printed circuit boards (FPCs) into irregularly shaped housings to achieve structural and functional integration has become an important trend in the electronics manufacturing industry. This process can save internal space in equipment and improve product integration and protection performance.
[0003] However, the manufacturing of FPC embedded irregular-shaped shells is constrained by material properties and molding processes. The substrate of FPC is typically polyimide, which has a high glass transition temperature and strong elastic memory effect. When bonding large curvatures or complex irregular shapes, the substrate is prone to elastic rebound, causing the FPC to shift within the mold cavity, leading to defects such as insufficient injection molding, circuit damage, or exposed copper. Existing preforming processes are insufficient to fully eliminate the internal stress of the substrate, failing to guarantee that the FPC maintains a stable geometric shape within the mold.
[0004] On the other hand, polyimide has low surface energy and strong chemical inertness, resulting in poor compatibility with commonly used thermoplastic resins such as polycarbonate. During conventional injection molding, the resin melt struggles to form effective molecular chain diffusion and entanglement with the FPC surface, leading to insufficient interfacial bonding strength and making the product prone to delamination during stress or environmental testing.
[0005] Furthermore, to fill complex thin-walled irregular structures, the injection molding process typically requires high injection and holding pressures. The filling of high-pressure melt introduces shear orientation stress into the polymer matrix. If holding pressure is applied directly before the melt has relaxed, internal stress is easily retained within the part, leading to warping after demolding. Simultaneously, if the fluid pressure during the holding phase directly acts on the delicate circuitry within the FPC, it may cause microstructural damage or changes in circuit resistance, affecting the stability of communication signal transmission. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a molding process for embedding flexible FPC communication lines in irregularly shaped housings, which solves the problems of positioning deviation caused by the elastic rebound of polyimide substrate, weak bonding force at the interface of heterogeneous materials, and warping and line damage caused by excessive internal stress in existing FPC embedding injection molding processes.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a molding process for embedding a flexible FPC communication line in an irregularly shaped housing, comprising the following steps:
[0008] S1. An interface-modified film is covered on one side of the FPC flexible circuit board, and a composite FPC with an interface layer is obtained by hot pressing; the interface-modified film is made of raw materials containing polyester thermoplastic polyurethane and 1,4-cyclohexanediethanol modified copolyester.
[0009] S2. Place the composite FPC into the preforming mold, close the mold and hold it under pressure at a temperature of 180℃-210℃ to cause viscoelastic creep of the FPC and interface layer to fit the mold cavity. Then, perform rapid cooling to fix the interface layer in a non-equilibrium glass state, and open the mold to obtain the preformed FPC.
[0010] S3. Place the preformed FPC into the injection mold and inject the thermoplastic resin melt; as the melt flows across the FPC surface, the interface layer is activated by the shear heat generated by the injection speed.
[0011] S4. When the filling rate of the injection mold cavity reaches 98% or more, stop the injection and set a delay time. After the melt and the internal stress of the FPC relax, apply holding pressure to compensate for shrinkage. After cooling, the FPC embedded irregular shell is obtained.
[0012] By adopting the above technical solution, this invention utilizes the viscoelastic properties of polymer materials and the principle of thermodynamic phase transition to achieve precise geometric locking and low-stress bonding of FPC. Its specific mechanism of action is as follows:
[0013] Step S2 utilizes a high-temperature pressure holding condition of 180℃ to 210℃ to place the polyimide substrate in the secondary transition region below the glass transition temperature. Under the synergistic effect of this temperature and stress field, the polyimide molecular chain segments undergo localized coordinated movement, resulting in stress relaxation. This transforms the elastic deformation of the FPC into irreversible viscoplastic deformation, thereby reducing the springback tendency of the FPC on irregular curved surfaces and ensuring its fitting accuracy in the mold cavity.
[0014] Secondly, the thermodynamic state of the interface layer is controlled through a rapid cooling process. When the interface layer, molten at high temperature, is rapidly cooled, the polymer chains cannot rearrange into a dense equilibrium structure in time, thus becoming fixed in a non-equilibrium glassy state (or a high-energy metastable state) with high free volume. In the subsequent injection molding stage, this high free volume state reduces the activation energy required for diffusion of the interface molecular chains. When the interface layer is subjected to shear heat from the injection melt, the chains can rapidly untangle and interdiffuse with the bulk resin melt, forming a dense physical entanglement network and improving the interfacial bonding strength.
[0015] The delayed holding pressure process set in step S4 matches the relaxation characteristics of the polymer melt. At the end of cavity filling, the melt molecular chains are in a highly shear-oriented state, and the FPC surface is subjected to significant hydrodynamic pressure. Setting a delay time allows the oriented molecular chain segments to deorient and relax, and makes the pressure distribution within the cavity more uniform. The subsequent holding pressure is mainly used to compensate for volume shrinkage, avoiding the freezing of excessive orientation stress and fluid impact stress inside the part, thereby reducing the molding internal stress of the irregular shell and improving the dimensional stability of the part and the reliability of the circuit.
[0016] Preferably, the interface-modified film is made from raw materials comprising the following parts by weight: 75-90 parts of polyester-type thermoplastic polyurethane; 10-25 parts of 1,4-cyclohexanediethanol-modified copolyester; and 0.2-0.5 parts of antioxidant.
[0017] By employing the above technical solution, polyester-based thermoplastic polyurethane provides toughness and adhesion to the polyimide substrate for the interface layer; 1,4-cyclohexanediethanol-modified copolyester, as an amorphous component, is used to adjust the glass transition temperature and melt viscosity of the system, improving its compatibility with the polycarbonate main resin. The combined use of these two components enables the interface material to fill micro-gaps at pre-forming temperatures while maintaining structural integrity under injection molding erosion.
[0018] Preferably, the polyester-type thermoplastic polyurethane has a Shore hardness of 90A-95A and a peak melting temperature of 165℃-175℃; in the 1,4-cyclohexanediethanol modified copolyester, the copolymer content of 1,4-cyclohexanediethanol is 30mol%-35mol% and the glass transition temperature is 80℃±5℃.
[0019] By adopting the above technical solution, the polyurethane with higher hardness and melting point gives the interface layer sufficient mechanical modulus, so that it can play a skeletal support role during demolding and transportation, and prevent the preformed FPC from deforming; the copolyester with a specific copolymer content has a solubility parameter similar to that of bisphenol A type polycarbonate, which, according to the principle of similar compatibility, is conducive to promoting the interdiffusion of molecular chains at the interface.
[0020] Preferably, the method for preparing the interface-modified film includes: uniformly mixing the polyester-type thermoplastic polyurethane, 1,4-cyclohexanediethanol-modified copolyester, and antioxidant, and then adding the mixture to a twin-screw extruder for melt blending and granulation at a temperature of 155℃-205℃; adding the resulting modified particles to a casting machine and casting them into a film through a T-die, with the die temperature controlled at 195℃-200℃ and the film thickness controlled at 0.15mm-0.30mm.
[0021] By adopting the above technical solutions, the strong shearing effect of twin-screw extrusion ensures that the two polymer components are uniformly dispersed at the microscale; the casting process can control the uniformity of film thickness and ensure the consistency of interfacial heat transfer during subsequent hot pressing and preforming processes.
[0022] Preferably, the hot-pressing composite process conditions are: hot-pressing temperature of 140℃-150℃, pressure of 0.5MPa-1.0MPa, and holding time of 5s-10s.
[0023] By adopting the above technical solution, the process window softens the interface film and physically anchors it to the FPC surface, while limiting the thermal degradation of the polymer and preserving the reactivity or physical properties of the interface material required in subsequent processes.
[0024] Preferably, the specific process parameters for mold closing and pressure holding are: mold closing and pressure holding pressure is 2MPa-5MPa, and pressure holding time is 20s-60s; wherein, when the heating temperature exceeds 200℃ or the pressure exceeds 4MPa, a limit control method is used to close the mold to control the interface layer thickness.
[0025] By adopting the above technical solution, the setting of the pressure holding parameters is intended to provide sufficient driving force to overcome the elastic modulus of the FPC substrate and promote molecular chain slippage; the limiting control method is used to prevent excessive loss of interface material under high temperature and high pressure, and to ensure that the thickness of the bonding layer meets the design requirements.
[0026] Preferably, the specific process parameters for the rapid cooling are: cooling rate ≥ 30℃ / s, cooling termination temperature ≤ 35℃; the rapid cooling is achieved by liquid nitrogen-assisted cooling or high-pressure refrigerant circulation.
[0027] By adopting the above technical solution, a cooling rate greater than 30℃ / s can effectively block the rearrangement process of polymer chain segments to the equilibrium conformation, and retain the free volume inside the material to the greatest extent, thereby obtaining a non-equilibrium glassy interface layer with high excess enthalpy.
[0028] Preferably, the specific process parameters for the shear activation injection molding are: the injection mold temperature is set to 80℃-100℃; and the injection speed is set to 80%-95% of the maximum injection speed of the injection molding machine when the melt flows through the FPC surface area.
[0029] By adopting the above technical solution, the temperature of the melt front and contact interface is rapidly increased by utilizing the shear friction heating effect under high injection speed. This causes the non-equilibrium interface layer to disorient and soften at the moment of contact, thereby activating the interface and avoiding the long molding cycle problem caused by relying on the overall high temperature of the mold.
[0030] Preferably, the specific process parameters for the delayed pressure holding are: the delay time is 0.2s-0.6s; the pressure holding pressure is 60MPa-90MPa; and the pressure holding time is 3s-5s.
[0031] By adopting the above technical solution, the delay time of 0.2 to 0.6 seconds is matched with the stress relaxation time scale of polycarbonate melt, which attenuates the melt pressure peak and partially recovers the oriented chain segments, thereby reducing the residual internal stress along the flow direction while maintaining pressure and compressing in the subsequent process.
[0032] Preferably, the substrate of the FPC flexible circuit board is a polyimide film with a glass transition temperature ≥280℃; the thermoplastic resin is bisphenol A type polycarbonate with a Vicat softening point ≥140℃.
[0033] By adopting the above technical solution, this process solves the problems of weak bonding and stress cracking in conventional processes by precisely controlling the thermal history and stress history of heterogeneous material combinations with high heat resistance.
[0034] This invention provides a molding process for embedding flexible FPC communication lines in irregularly shaped housings. It offers the following advantages:
[0035] 1. This invention effectively solves the elastic rebound problem of high-rigidity polyimide substrates when bonding to irregular curved surfaces by implementing high-temperature creep and rapid cooling shaping processes during the preforming stage. A temperature field of 180℃ to 210℃ is used to induce stress relaxation in the molecular chain segments of the substrate, transforming reversible elastic deformation into irreversible viscoplastic deformation. Rapid cooling is then used to quickly fix the material state, thereby ensuring precise bonding between the preformed FPC and the injection mold cavity, improving the positioning accuracy of subsequent injection molding, and avoiding defects such as pressure marks or insufficient adhesive caused by FPC springback.
[0036] 2. This invention employs an interface-modified film comprising polyester-type thermoplastic polyurethane and 1,4-cyclohexanediethanol-modified copolyester, combined with a shear-activated injection molding process, significantly improving the interfacial bonding strength between heterogeneous materials. After rapid cooling, this interface material is in a high-free-volume, non-equilibrium glass state. Under the shear heat of the injection melt, the diffusion activation energy is reduced, enabling rapid molecular chain interdiffusion with polycarbonate resin to form a physical interpenetrating network. This achieves a strong, integrated bond between the FPC and the irregularly shaped shell, significantly improving peel strength.
[0037] 3. This invention introduces a delayed holding pressure control strategy, which effectively reduces the residual internal stress of the embedded irregular-shaped housing and ensures the electrical stability of the circuit. By setting a delay window of 0.2 to 0.6 seconds between the end of filling and the holding pressure stage, highly oriented melt molecular chains are allowed to relax and recover, and the peak hydrodynamic pressure in the mold cavity is attenuated, thereby suppressing warping deformation after part cooling, and preventing microscopic fracture or resistance drift of FPC circuit conductors caused by high-pressure impact. Attached Figure Description
[0038] Figure 1 The following is a comparison chart of the geometric stability test data of the present invention; wherein, Figure (a) is a comparison chart of the average rebound angle of each group of samples, and Figure (b) is a comparison chart of the average shape retention rate of each group of samples.
[0039] Figure 2 This is a comparison diagram of the 90-degree peel strength and error distribution of the present invention;
[0040] Figure 3 The figures are comparison charts of the dimensional accuracy test data of the finished irregular shell of the present invention; wherein, Figure (a) is a comparison chart of the average deviation (mm) of the FPC embedding position, and Figure (b) is a comparison chart of the average warping deformation (mm) of the finished shell.
[0041] Figure 4 The following is a comparison chart of electrical performance stability test data of the present invention; wherein, Figure (a) is a comparison chart of the average change rate (%) of DC resistance of key lines, and Figure (b) is a statistical chart of the number of line open circuit failures. Detailed Implementation
[0042] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0043] To achieve the above objectives, the present invention provides the following technical solution:
[0044] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below with reference to specific embodiments. The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher products.
[0045] Polycarbonate (PC): Commercially available general-purpose bisphenol A type polycarbonate with a melt flow rate of 15 g / 10 min (300℃ / 1.2 kg) and a Vicat softening point of 143℃.
[0046] Polyimide (PI) film: Commercially available modified polyimide substrate for FPC, 25 μm thick, with a glass transition temperature of 285 °C.
[0047] Polyester-based thermoplastic polyurethane (TPU): Commercially available product, a polyadipate-based thermoplastic polyurethane elastomer with a Shore hardness of 90A and a peak melting temperature of 170℃.
[0048] 1,4-Cyclohexanediethanol-modified copolyester (PETG): Commercially available amorphous copolyester with a 1,4-cyclohexanediethanol copolymer content of 30 mol%-35 mol% and a glass transition temperature of 80 °C.
[0049] Antioxidant 1010, CAS No. 6683-19-8.
[0050] Preparation Example 1:
[0051] This preparation example provides a method for preparing an interface-modified thin film, including the following steps:
[0052] Weigh 85 parts by weight of dried polyester thermoplastic polyurethane, 15 parts by weight of 1,4-cyclohexanediethanol modified copolyester and 0.2 parts by weight of antioxidant 1010, and mix them evenly in a high-speed mixer to obtain a premix.
[0053] The premixed material was added to a twin-screw extruder for melt blending and granulation. The temperatures of each zone of the extruder were set as follows: zone 1 160℃, zone 2 175℃, zone 3 190℃, zone 4 200℃, and die head 195℃. The screw speed was 250 rpm. The modified particles were obtained by pelletizing.
[0054] Modified particles are added to a single-screw casting machine and cast into a film through a T-die. The die temperature is 195℃, the casting roller temperature is controlled at 25℃, and the traction speed is adapted to control the film thickness at 0.20mm. The film is then wound up to obtain the interface-modified film A1.
[0055] Preparation Example 2:
[0056] This preparation example provides a method for preparing an interface-modified thin film, including the following steps:
[0057] Weigh 75 parts by weight of dried polyester thermoplastic polyurethane, 25 parts by weight of 1,4-cyclohexanediethanol modified copolyester and 0.5 parts by weight of antioxidant 1010, and mix them evenly in a high-speed mixer to obtain a premix.
[0058] The premixed material was added to a twin-screw extruder for melt blending and granulation. The temperatures of each zone of the extruder were set as follows: zone 1 155℃, zone 2 170℃, zone 3 185℃, zone 4 195℃, and die head 200℃. The screw speed was 280 rpm. The modified particles were obtained by pelletizing.
[0059] Modified particles are added to a single-screw casting machine and cast into a film through a T-die. The die temperature is 195℃, the casting roller temperature is controlled at 20℃, and the traction speed is adapted to control the film thickness at 0.15mm. The film is then wound up to obtain the interface-modified film A2.
[0060] Preparation Example 3:
[0061] This preparation example provides a method for preparing an interface-modified thin film, including the following steps:
[0062] Weigh 90 parts by weight of dried polyester thermoplastic polyurethane, 10 parts by weight of 1,4-cyclohexanediethanol modified copolyester and 0.2 parts by weight of antioxidant 1010, and mix them evenly in a high-speed mixer to obtain a premix.
[0063] The premixed material was added to a twin-screw extruder for melt blending and granulation. The temperatures of each zone of the extruder were set as follows: zone 1 165℃, zone 2 180℃, zone 3 195℃, zone 4 205℃, and die head 200℃. The screw speed was 220 rpm. The modified particles were obtained by pelletizing.
[0064] Modified particles are added to a single-screw casting machine and cast into a film through a T-die. The die temperature is 200℃, the casting roller temperature is controlled at 30℃, and the traction speed is adapted to control the film thickness at 0.30mm. The film is then wound up to obtain the interface-modified film A3.
[0065] Example 1:
[0066] This embodiment provides a molding process for embedding flexible FPC communication lines in an irregularly shaped housing, including the following steps:
[0067] (1) Take the cut FPC flexible circuit board, cover the side away from the line with the interface modified film A1 obtained in Preparation Example 1, place it in a hot press for lamination and composite, the hot pressing temperature is 145℃, the pressure is 0.8MPa, the holding time is 8s, and after cooling, a composite FPC with an interface layer is obtained.
[0068] (2) Place the composite FPC into a preformed mold with an irregular cavity, heat the mold to 195°C, close the mold and apply a pressure of 3MPa, maintain constant temperature and pressure for 40s, so that the FPC creeps and fits into the cavity; then start liquid nitrogen-assisted cooling, and rapidly cool the mold temperature to 35°C at a rate of 45°C / s, open the mold and take out the preformed FPC. At this time, the interface layer is in a non-equilibrium glass state.
[0069] (3) Place the preformed FPC into the injection mold cavity. The main injection resin is bisphenol A polycarbonate. The mold temperature is set to 90°C and the barrel nozzle temperature is 290°C. Start the injection and control the injection speed curve. When the melt flows through the FPC surface area, the injection speed is set to 90% of the maximum injection speed of the injection molding machine. The interface layer is activated by shear heat.
[0070] (4) When the mold cavity filling rate reaches 98%, stop the injection and set a delay time of 0.4s. During this period, no holding pressure is applied. After the delay ends, immediately apply a holding pressure of 80MPa and hold it for 4s. Then cool for 15s and open the mold to eject the FPC embedded irregular shell.
[0071] Example 2:
[0072] This embodiment provides a molding process for embedding flexible FPC communication lines in an irregularly shaped housing, including the following steps:
[0073] (1) Take the cut FPC flexible circuit board, cover the side away from the line with the interface modified film A2 obtained in Preparation Example 2, place it in a hot press for lamination and composite, the hot pressing temperature is 140℃, the pressure is 0.5MPa, the holding time is 5s, and after cooling, a composite FPC with an interface layer is obtained.
[0074] (2) Place the composite FPC into a preformed mold with an irregular cavity, heat the mold to 180°C, close the mold and apply 2MPa pressure, maintain constant temperature and pressure for 20s, so that the FPC creeps and fits into the cavity; then start the high-pressure refrigerant circulation, cool the mold temperature to 30°C at a rate of 30°C / s, open the mold and take out the preformed FPC. At this time, the interface layer is in a non-equilibrium glass state.
[0075] (3) Place the preformed FPC into the injection mold cavity. The main injection resin is bisphenol A polycarbonate. The mold temperature is set to 80°C and the barrel nozzle temperature is 285°C. Start the injection and control the injection speed curve. When the melt flows through the FPC surface area, the injection speed is set to 80% of the maximum injection speed of the injection molding machine. The interface layer is activated by shear heat.
[0076] (4) When the mold cavity filling rate reaches 98%, stop the injection and set a delay time of 0.2s. During this period, no holding pressure is applied. After the delay ends, immediately apply a holding pressure of 60MPa and hold it for 3s. Then cool for 12s and open the mold to eject the FPC embedded irregular shell.
[0077] Example 3:
[0078] This embodiment provides a molding process for embedding flexible FPC communication lines in an irregularly shaped housing, including the following steps:
[0079] (1) Take the cut FPC flexible circuit board, cover the side away from the line with the interface modified film A3 obtained in Preparation Example 3, place it in a hot press for lamination and composite, the hot pressing temperature is 150℃, the pressure is 1.0MPa, the holding time is 10s, and after cooling, a composite FPC with an interface layer is obtained.
[0080] (2) Place the composite FPC into a preformed mold with an irregular cavity, heat the mold to 210°C, close the mold and apply a pressure of 5MPa, maintain constant temperature and pressure for 60s, so that the FPC creeps and fits into the cavity; then start liquid nitrogen-assisted cooling, and rapidly cool the mold temperature to 25°C at a rate of 60°C / s, open the mold and take out the preformed FPC. At this time, the interface layer is in a non-equilibrium glass state.
[0081] (3) Place the preformed FPC into the injection mold cavity. The main injection resin is bisphenol A polycarbonate. The mold temperature is set to 100°C and the barrel nozzle temperature is 300°C. Start the injection and control the injection speed curve. When the melt flows through the FPC surface area, the injection speed is set to 95% of the maximum injection speed of the injection molding machine. The interface layer is activated by shear heat.
[0082] (4) When the mold cavity filling rate reaches 98%, stop the injection and set a delay time of 0.6s. During this period, no holding pressure is applied. After the delay ends, immediately apply a holding pressure of 90MPa and hold it for 5s. Then cool for 20s and open the mold to eject the FPC embedded irregular shell.
[0083] Example 4:
[0084] This embodiment provides a molding process for embedding flexible FPC communication lines in an irregularly shaped housing, including the following steps:
[0085] (1) Take the cut FPC flexible circuit board, cover the side away from the line with the interface modified film A1 obtained in Preparation Example 1, place it in a hot press for lamination and composite, the hot pressing temperature is 145℃, the pressure is 0.8MPa, the holding time is 8s, and after cooling, a composite FPC with an interface layer is obtained.
[0086] (2) Place the composite FPC into a preformed mold with an irregular cavity, heat the mold to 200°C, close the mold and apply a pressure of 4MPa, maintain constant temperature and pressure for 30s, so that the FPC creeps and fits into the cavity; then start the cooling system to rapidly cool the mold temperature to 40°C at a rate of 40°C / s, open the mold and take out the preformed FPC. At this time, the interface layer is in a non-equilibrium glass state.
[0087] (3) Place the preformed FPC into the injection mold cavity. The main injection resin is bisphenol A polycarbonate. The mold temperature is set to 95°C and the barrel nozzle temperature is 295°C. Start the injection and control the injection speed curve. When the melt flows through the FPC surface area, the injection speed is set to 85% of the maximum injection speed of the injection molding machine. The interface layer is activated by shear heat.
[0088] (4) When the mold cavity filling rate reaches 98%, stop the injection and set a delay time of 0.5s. During this period, no holding pressure is applied. After the delay ends, immediately apply a holding pressure of 85MPa and hold it for 4s. Then cool for 15s and open the mold to eject the FPC embedded irregular shell.
[0089] Comparative Example 1:
[0090] Compared with Example 1, the difference is that in step (1), the interface modified film A1 was not composited, but the untreated FPC was directly placed into the preform mold for subsequent steps, and the rest were the same.
[0091] Comparative Example 2:
[0092] Compared with Example 1, the difference is that the cooling method in step (2) is different. Instead of using liquid nitrogen for rapid cooling, the mold is allowed to cool naturally in the air to 35°C after heating is stopped (the average cooling rate is about 2°C / s). The rest are the same.
[0093] Comparative Example 3:
[0094] Compared with Example 1, the difference is that the pre-forming heating temperature in step (2) is set to 150°C, while the rest are the same.
[0095] Comparative Example 4:
[0096] Compared with Example 1, the difference is that the pre-forming heating temperature in step (2) is set to 285°C, while the rest are the same.
[0097] Comparative Example 5:
[0098] Compared with Example 1, the difference lies in the injection speed in step (3). In this comparative example, the injection speed is set to 30% of the maximum injection speed of the injection molding machine when the melt flows through the surface area of the FPC, and the rest are the same.
[0099] Comparative Example 6:
[0100] Compared with Example 1, the difference is that the delayed pressure holding procedure is cancelled in step (4). After the cavity filling rate reaches 98%, a pressure holding pressure of 80MPa is applied immediately. All other aspects are the same.
[0101] Test Example 1:
[0102] This test case aims to verify the geometric stability of FPC under different thermal histories and confirm the actual effect of high-temperature creep forming process on eliminating internal stress in PI substrate.
[0103] Ten samples were randomly selected from each of the preformed FPC intermediates (i.e., semi-finished products that have not yet undergone injection molding) obtained in Examples 1 to 4 and Comparative Example 3 as test subjects. The theoretical bending design angle of the preformed mold was set to 90° (i.e., the included angle between the two planes on both sides of the R angle is 90°).
[0104] All samples were placed in a constant temperature and humidity environment (23±2℃, 50±5%RH) for 24 hours to eliminate the instantaneous elastic recovery after demolding and to bring the material to a state of stress relaxation equilibrium.
[0105] The actual bending angle of the sample is measured non-contactly using an image measuring instrument. During measurement, one plane of the FPC bending area is used as a reference, and the actual included angle value of the other plane is measured and recorded as follows. .
[0106] According to the formula Calculate the rebound angle using the formula. Calculate the shape retention rate and record the arithmetic mean and standard deviation of each data set.
[0107] The experimental data are shown in Table 1:
[0108] Table 1 Test data on springback angle and shape retention
[0109] Group Sample size (n) Maximum measured angle Minimum measured angle Average rebound angle Angular standard deviation Average shape retention (%) Example 1 10 90.85 90.12 0.43 0.21 99.52 Example 2 10 92.41 91.05 1.62 0.45 98.20 Example 3 10 90.55 90.05 0.28 0.14 99.69 Example 4 10 91.12 90.35 0.65 0.26 99.28 Comparative Example 3 10 115.40 109.80 22.35 2.15 75.17
[0110] in conclusion:
[0111] According to Table 1 and Figure 1 The data showed that the average springback angle of samples 1, 3, and 4 was controlled within 1°, with a shape retention rate exceeding 99%, while the average springback angle of Comparative Example 3 was as high as 22.35°, with a shape retention rate of only 75.17%. This significant difference in data confirms the decisive role of the viscoelastic creep shaping mechanism in FPC geometric locking.
[0112] Comparative Example 3 used a pre-forming temperature of 150℃. Although this temperature is higher than the softening point of TPU, it is far lower than the glass transition temperature of the PI substrate and does not reach the energy level at which significant lattice slip occurs in the copper foil circuitry. Under these conditions, the deformation of the FPC mainly consists of elastic deformations such as bond angle twisting and bond length stretching of the polymer chain segments. When the external force is removed, the PI molecular chain is in a random coil conformation with the maximum recovery entropy, releasing the stored elastic potential energy, resulting in huge rebound. This makes it impossible for the FPC to fit into the injection mold cavity, which can easily cause pressure damage or glue leakage in subsequent processes.
[0113] Conversely, the example group activated the coordinated movement of molecular chain segments in the amorphous region of PI by applying a prolonged isothermal holding pressure within the range of 180°C to 210°C. Stress relaxation and structural reorganization were then achieved using the fully molten interface layer, transforming elastic deformation into irreversible plastic deformation. Simultaneously, this thermal history process promoted the recrystallization and softening of the copper foil circuitry, reducing the yield stress of the metal layer. The cooled interface-modified layer further acted as a rigid framework, physically locking in this creeped geometry. Data from Example 2 shows that even at the lower limit of the process window (180°C / 20s), its springback control (1.62°) was significantly better than conventional processes, demonstrating that the thermodynamic parameter window set in this invention effectively achieved the transition from elastic dominance to viscoplastic dominance.
[0114] Test Example 2:
[0115] This test case aims to verify whether the liquid nitrogen quenching process successfully constructs a non-equilibrium glassy interface with high free volume by comparing the thermodynamic states of interface materials treated with different cooling rates through differential scanning calorimetry (DSC).
[0116] For the preformed FPC samples prepared in Examples 1, 2, 4, and Comparative Example 2, approximately 5 mg to 8 mg of polymer flakes were carefully scraped from the surface of the interface modification layer using a scalpel blade as test samples. The sampling process avoided the copper wiring area, collecting only the polymer interface layer material.
[0117] The sample was sealed in an aluminum crucible and tested using a differential scanning calorimeter. The experimental atmosphere was high-purity nitrogen, and the gas flow rate was set to 50 mL / min.
[0118] The heating program was set as follows: the sample was first held isothermally at 0℃ for 3 minutes, and then heated to 200℃ at a heating rate of 20℃ / min. The heat flow curve during the first heating process was recorded, with a focus on monitoring the thermal effects in the glass transition temperature (Tg) region.
[0119] The DSC curve was integrated using general analysis software to determine the area of the endothermic peak in the glass transition region, calculate the excess enthalpy caused by structural relaxation, and determine the midpoint temperature of the glass transition.
[0120] The experimental data are shown in Table 2:
[0121] Table 2 Summary of DSC thermal analysis data for interface layer materials
[0122] Group Sample mass (mg) Glass transition midpoint temperature (°C) Relaxation peak temperature (°C) Excess enthalpy (J / g) State determination Example 1 5.42 82.14 82.65 0.35 Non-equilibrium state Example 2 6.10 81.85 83.20 0.82 Non-equilibrium state Example 4 5.88 82.33 83.05 0.54 Non-equilibrium state Comparative Example 2 6.35 85.92 88.45 7.68 equilibrium state
[0123] in conclusion:
[0124] According to the data in Table 2, the sample of Comparative Example 2 exhibited an excess enthalpy of up to 7.68 J / g in the glass transition region, accompanied by a significant relaxation peak (peak temperature 88.45 °C), while the excess enthalpy of Examples 1, 2, and 4 was all below 1.0 J / g, and the DSC curves showed typical rapid quenching glassy characteristics.
[0125] Data shows that Comparative Example 2, using natural cooling, has a relatively low cooling rate (approximately 2°C / s). This allows sufficient time for the polymer chains to rearrange and densely pack, resulting in physical aging and causing the material to enter a thermodynamic equilibrium state with low free volume and low internal energy. During subsequent injection molding heating, this dense structure needs to absorb additional heat (manifested as a large endothermic peak) to overcome intermolecular forces, which significantly increases the activation energy barrier for molecular chain motion.
[0126] Conversely, the example group used liquid nitrogen or a refrigerant to rapidly freeze the random coil conformation of the interface material in its molten state (>30°C / s), instantly freezing it. The measured low excess enthalpy confirmed that the material retained a large amount of free volume and was in a high-energy metastable state. The molecular chain segments in this non-equilibrium state exhibit extremely high mobility, eliminating the need to overcome the additional energy barrier caused by physical aging. During the injection molding stage, when subjected to high-temperature melt shearing, the interface layer in the examples could rapidly undergo chain segment untangling and diffusion using its high free volume, instantly forming an interpenetrating network with the host resin following the creeping theory, thus confirming the effectiveness of the shear activation mechanism of the non-equilibrium interface.
[0127] Test Example 3:
[0128] This test case aims to quantitatively evaluate the interfacial bonding force between FPC and the injection molding host resin. By comparing the peel strength and failure mode under different process conditions, it verifies the influence of shear thermal activation, interdiffusion and delayed relaxation effects on the construction of interfacial entangled networks, and conversely verifies the necessity of low-temperature creep forming window for maintaining interfacial activity.
[0129] From the FPC embedded irregular-shaped housing products prepared in Examples 1 to 4 and Comparative Examples 1, 2, 4, 5, and 6, flat areas were selected as sampling points. The samples were cut into strips with a width of 10 mm using a precision cutting machine to ensure that the FPC circuit layer was not physically damaged, and to retain about 20 mm of FPC unbonded to the resin as a clamping end.
[0130] Fix the sample onto the special test fixture of the universal testing machine. Use the self-aligning fixture to hold the injection-molded substrate portion, and hold the FPC peeling end in the upper fixture, keeping the peeling angle perpendicular to the substrate surface at all times (90°±2°).
[0131] Set the tensile rate to 50 mm / min, start the test program, and continuously record the force-displacement curve during the peeling process. Set the effective peel stroke to 30 mm, and the system automatically discards the unstable zone data in the initial 5 mm. Divide the average load within the remaining stroke by the sample width to calculate the peel strength (N / cm).
[0132] After the test, the failure mode of the peeling interface was observed using a high-magnification optical microscope and recorded as interface failure, cohesive failure, or material degradation failure.
[0133] The experimental data are shown in Table 3:
[0134] Table 3. Test data of 90-degree peel strength and failure mode of samples.
[0135] Group Sample size Average peel strength (N / cm) Strength Standard Deviation Minimum value (N / cm) Maximum value (N / cm) Main destruction modes Example 1 8 12.45 0.82 11.03 13.62 100% cohesion destruction Example 2 8 11.23 0.95 9.85 12.55 90% cohesion destruction Example 3 8 13.08 0.64 12.11 14.15 100% cohesion destruction Example 4 8 11.92 0.77 10.88 13.10 100% cohesion destruction Comparative Example 1 8 0.35 0.08 0.22 0.48 Interface destruction Comparative Example 2 8 4.12 1.25 2.55 5.80 Interface damage / hybrid damage Comparative Example 4 8 1.05 0.35 0.60 1.55 Interface damage (accompanied by carbonization) Comparative Example 5 8 3.88 0.55 3.10 4.65 Interface destruction Comparative Example 6 8 7.65 2.15 4.20 10.10 Mixed destruction
[0136] in conclusion:
[0137] According to Table 3 and Figure 2 The data showed that the average peel strength of the example group exceeded 11 N / cm, and the failure mode was mainly cohesive failure. The strength of Comparative Example 1 was only 0.35 N / cm, indicating that the PC resin and the PI substrate lacked thermodynamic compatibility.
[0138] Comparative Example 4 exhibited a peel strength of 1.05 N / cm and showed signs of carbonization at the interface. This was because Comparative Example 4 was pre-molded at 285°C, close to the glass transition temperature of PI, which exceeded the thermal stability window of the interface modification components, leading to thermal degradation and breakage of the polymer chains and the formation of a weak boundary layer.
[0139] The peel strength of Comparative Example 2 (without quenching) and Comparative Example 5 (low injection rate) was approximately 4 N / cm, with interface damage being the primary occurrence. In Comparative Example 2, the activation energy barrier of the equilibrium interface layer was too high, and in Comparative Example 5, the shear rate was insufficient to provide adequate frictional enthalpy. Neither of these methods achieved the transition of the interface layer from a glassy state to a near-liquid state, hindering the diffusion of molecular chains towards the PC melt side.
[0140] Comparative Example 6 (without delayed pressure holding) showed a peel strength of 7.65 N / cm, with a large standard deviation and mixed failure. At the moment of completion of filling, the interfacial polymer chains were highly oriented along the flow direction. If pressure was held immediately, the chain segments were frozen in an extended state and could not retract to form random coils. This non-entangled structure reduced the density of physical entanglement points and left residual orientation stress, leading to decreased bonding stability. The Example group, by delaying pressure holding to match the relaxation time of the molecular chains, promoted the completion of chain segment entanglement and constructed a dense physical connection network.
[0141] Test Example 4:
[0142] Twelve samples were randomly selected from each of the FPC embedded irregular shell products prepared in Examples 1, 3, Comparative Example 3 (low temperature preforming) and Comparative Example 6 (no delayed pressure holding) as test objects.
[0143] The sample is fixed on the inspection platform of a coordinate measuring machine, and a workpiece coordinate system based on the rigid features of the shell (positioning pins or edges) is established. The centers of three iconic pads on the FPC circuit layer are selected as measurement points, their actual spatial coordinates are measured, and compared with the theoretical coordinates of the CAD model. The three-dimensional spatial position deviation is calculated, and the maximum deviation value of the three points is taken as the final position deviation of the sample.
[0144] The sample is placed concave-side down on a high-precision marble testing platform, and a laser displacement sensor is used to perform a grid-like scan of the back plane of the shell. The height difference of each point on the surface relative to the marble plane is recorded, and the maximum height difference is taken as the warping deformation of the sample.
[0145] The experimental data are shown in Table 4:
[0146] Table 4. Test data on position deviation and warping deformation
[0147] Group Sample size Average positional deviation (mm) Maximum positional deviation (mm) Standard deviation (mm) Average warpage (mm) Maximum warpage (mm) Standard deviation of warpage (mm) Example 1 12 0.082 0.115 0.018 0.125 0.168 0.024 Example 3 12 0.075 0.102 0.015 0.110 0.145 0.021 Comparative Example 3 12 0.845 1.220 0.285 0.685 0.950 0.155 Comparative Example 6 12 0.095 0.130 0.022 0.542 0.780 0.110
[0148] in conclusion:
[0149] According to Table 4 and Figure 3 The data shows that the average positional deviation of Comparative Example 3 was as high as 0.845 mm, and some samples had deviations exceeding 1.2 mm, significantly exceeding the tolerance range of ±0.15 mm typically required for precision structural parts. This is attributed to the low-temperature preforming process of Comparative Example 3 at 150°C, which failed to induce sufficient viscoelastic creep in the PI substrate, resulting in significant elastic potential energy remaining within the FPC. During mold closing and high-pressure melt filling, the springback-prone FPC could not adhere tightly to the mold cavity wall, leading to displacement and misalignment under fluid impact. Simultaneously, this springback stress, combined with injection shrinkage stress, resulted in an average warpage of up to 0.685 mm.
[0150] Examples 1 and 3 both exhibited excellent performance across all metrics, with positional deviation controlled at approximately 0.08 mm and warpage below 0.13 mm. This confirms that the creep forming process performed in the 195℃-210℃ range successfully eliminated the elastic memory of the PI substrate, enabling the FPC to precisely fit the cavity without adhesive fixation, thus achieving geometric positioning lock-in.
[0151] The data from Comparative Example 6 showed that its positional deviation (0.095 mm) was comparable to that of the Example Group, but its average warpage (0.542 mm) was more than four times that of the Example Group. Analysis indicated that although Comparative Example 6 underwent effective high-temperature preforming, solving the FPC positioning problem, the elimination of delayed holding pressure during the injection molding stage resulted in the high shear orientation stress after melt filling being forcibly frozen within the system by the immediately applied high holding pressure (80 MPa). This unrelaxed anisotropic internal stress was released after demolding and cooling, leading to severe matrix warpage. The Example Group, by introducing a delayed holding pressure window, allowed entropy recovery of polymer segments in the molten state, effectively reducing residual internal stress and thus ensuring the dimensional stability of the final product.
[0152] Test Example 5:
[0153] Twenty samples were randomly selected from each of the FPC embedded irregular-shaped shell products prepared in Examples 1, 3, Comparative Example 2 (without rapid cooling) and Comparative Example 6 (without delayed pressure holding).
[0154] All samples were placed in a programmable thermal shock test chamber, and the cyclic conditions were set as follows: the temperature in the low temperature zone was -40℃, the temperature in the high temperature zone was 85℃, the residence time in both the high and low temperatures was 30 minutes, and the transition time between the two zones was less than 10 seconds.
[0155] Start the test program and pause the test after completing 100 and 300 cycles, respectively. Remove the samples and allow them to recover at room temperature for 2 hours. Then, examine the bonding edge between the FPC and the injection resin using a stereomicroscope (30X magnification).
[0156] Record the failure details. The failure criteria are: visible delamination or blistering exceeding 0.5 mm in length at the interface, or continuous microcracks observed under a microscope. Calculate the cumulative number of failures and the failure rate for each node.
[0157] The experimental data are shown in Table 5:
[0158] Table 5 Failure data due to thermal shock cycles
[0159] Group Total number of samples 100 cycle failures Description of 100-cycle failure phenomenon 300 cycle failures (cumulative) Failure rate over 300 cycles (%) Key characteristics of final failure Example 1 20 0 No obvious abnormalities 0 0.0 Complete interface Example 3 20 0 No obvious abnormalities 1 5.0 Localized microbubbling Comparative Example 2 20 4 Slight cracks at the edges 13 65.0 Large-area layered peeling Comparative Example 6 20 2 Tiny cracks in the corner 9 45.0 Interface fracture / crack propagation
[0160] in conclusion:
[0161] According to the data in Table 5, the failure rate of Examples 1 and 3 was controlled within 5% after 300 cycles. The examples constructed an interpenetrating physical entanglement network through shear activation and delayed relaxation. This network exhibited strong bonding, and the elastic modulus of the interface modification layer was between that of PC and PI, thus alleviating the interfacial shear stress caused by the mismatch in thermal expansion coefficients between the materials.
[0162] Comparative Example 2 showed a cumulative failure rate of 65.0%, mainly manifested as delamination. Because its interface layer was in thermodynamic equilibrium before injection molding, the molecular chain diffusion depth was insufficient, and no effective anchoring was formed, making it unable to resist repeated alternating thermal stress.
[0163] Comparative Example 6 showed a failure rate of 45.0%, characterized by crack propagation. Although its initial bond strength was acceptable, the lack of delayed pressure holding resulted in the interfacial polymer chains being frozen in a highly oriented state, leading to significant residual internal stress. During thermal shock, the combined environmental stress and residual material stress accelerated the breakage and untangling of the polymer chains. Data demonstrates that a sufficiently relaxed, low-stress entangled network is crucial for ensuring long-term reliability.
[0164] Test Example 6:
[0165] During the preparation process of Examples 1, 3, Comparative Example 3 (low temperature preforming) and Comparative Example 6 (no delayed holding pressure), 20 preformed FPC intermediates were randomly selected from each group before the injection molding and rheological activation steps.
[0166] Using a precision digital micro-ohmmeter, the initial DC resistance of a specified critical signal line on the FPC was measured using the Kelvin four-wire method, and denoted as . The selected circuitry includes fine-pitch copper foil circuitry with bends.
[0167] After measurement The sample is then fed into the injection mold to complete the subsequent injection molding process. After cooling and demolding, the final resistance value of the same circuit is measured again using the same equipment and recorded as... For samples with open circuits, the resistance value is recorded as... .
[0168] According to the formula Calculate the resistance change rate. If a sample is open-circuited, it is considered a functional failure. Calculate the average resistance change rate (excluding open-circuit samples) and the number of open-circuit failures for each group.
[0169] The experimental data are shown in Table 6:
[0170] Table 6 Test data on the change rate of circuit resistance before and after injection molding.
[0171] Group Sample size Initial resistance mean (m) ) Final resistance mean (m) ) Average rate of change (%) Maximum rate of change (%) Number of circuit failures Example 1 20 145.2 146.8 1.12 2.45 0 Example 3 20 148.5 149.9 0.95 1.88 0 Comparative Example 3 20 146.1 185.4 26.85 158.20 5 Comparative Example 6 20 144.8 153.2 5.82 12.65 1
[0172] in conclusion:
[0173] According to Table 6 and Figure 4 According to the data, the resistance change rate of the example group was controlled within 1.2%, with no open circuit failure. The interface modification layer plays a buffering role during injection molding, absorbing the shear impact force of the melt flow and maintaining the electrical integrity of the copper foil circuit.
[0174] Comparative Example 3 showed 5 open circuits, and the average resistance of the remaining samples increased by 26.85%. Based on the conclusions of Test Example 1, Comparative Example 3, due to low-temperature preforming, experienced FPC springback, failing to fit the mold cavity during mold closing, resulting in localized compression by the mold or folding under melt pressure. Mechanical damage led to a reduction in the cross-sectional area of the copper foil or circuit melting.
[0175] Although Comparative Example 6 had accurate positioning, its resistance change rate (5.82%) was higher than that of Example Group, and it also had one open circuit. This is because the delayed holding pressure step was missing. At the moment the cavity was filled, the kinetic energy of the melt was converted into hydrostatic pressure, and the immediately applied high-pressure holding pressure impacted the FPC in its high-temperature softened state, causing microscopic plastic tensile deformation of the copper foil circuit. The delayed holding pressure introduced in Example Group allowed the pressure peak to decay, avoiding the impact of instantaneous impact on the precision circuit.
[0176] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A molding process for embedding flexible FPC communication lines in an irregularly shaped housing, characterized in that, Includes the following steps: An interface-modified film is coated on one side of an FPC flexible circuit board, and then hot-pressed to obtain a composite FPC with an interface layer. The interface-modified film is made from raw materials comprising polyester-type thermoplastic polyurethane and 1,4-cyclohexanediethanol-modified copolyester. The composite FPC is placed into a preform mold and pressed at a temperature of 180℃-210℃ to cause viscoelastic creep of the FPC and interface layer to conform to the mold cavity. Then, a rapid cooling treatment is performed to fix the interface layer in a non-equilibrium glass state. The mold is then opened to obtain the preformed FPC. The preformed FPC is placed into the injection mold, and the thermoplastic resin melt is injected. The interface layer is activated by the shear heat generated by the injection speed when the melt flows across the FPC surface; When the cavity filling rate of the injection mold reaches more than 98%, the injection is stopped and a delay time is set. After the melt and the internal stress of the FPC relax, a holding pressure is applied to compensate for shrinkage. After cooling, the FPC embedded irregular shell is obtained.
2. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 1, characterized in that, The interface-modified film is made from raw materials comprising the following parts by weight: 75-90 parts of polyester-type thermoplastic polyurethane; 10-25 parts of 1,4-cyclohexanediethanol-modified copolyester; 0.2-0.5 parts of antioxidant 1010.
3. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 2, characterized in that, The polyester-type thermoplastic polyurethane has a Shore hardness of 90A-95A and a peak melting temperature of 165℃-175℃; the 1,4-cyclohexanediethanol modified copolyester has a copolymer content of 30mol%-35mol% and a glass transition temperature of 80℃±5℃.
4. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 2, characterized in that, The method for preparing the interface-modified thin film includes: The polyester-type thermoplastic polyurethane, 1,4-cyclohexanediethanol modified copolyester, and antioxidant 1010 are mixed evenly and then added to a twin-screw extruder for melt blending and granulation at a temperature of 155℃-205℃. The resulting modified particles are added to a casting machine and cast into a film through a T-die, with the die temperature controlled at 195℃-200℃ and the film thickness controlled at 0.15mm-0.30mm.
5. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 1, characterized in that, The hot-pressing composite process conditions are as follows: hot-pressing temperature is 140℃-150℃, pressure is 0.5MPa-1.0MPa, and holding time is 5s-10s.
6. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 1, characterized in that, The specific process parameters for mold closing and pressure holding are as follows: The mold closing pressure is 2MPa-5MPa, and the holding time is 20s-60s; When the heating temperature exceeds 200℃ or the pressure exceeds 4MPa, a limit control method is used to close the mold to control the thickness of the interface layer.
7. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 1, characterized in that, The specific process parameters for the rapid cooling are as follows: The cooling rate is ≥30℃ / s, and the cooling termination temperature is ≤35℃; the rapid cooling is achieved by liquid nitrogen-assisted cooling or high-pressure refrigerant circulation.
8. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 1, characterized in that, The specific process parameters for the shear-activated injection molding are as follows: The injection mold temperature is set to 80℃-100℃; When the melt flows through the surface area of the FPC, the injection speed is set to 80%-95% of the maximum injection speed of the injection molding machine.
9. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 1, characterized in that, The specific process parameters for the delayed pressure holding are as follows: The delay time is 0.2s-0.6s; The pressure holding pressure is 60MPa-90MPa, and the pressure holding time is 3s-5s.
10. The molding process for embedding a flexible FPC communication line in an irregularly shaped housing according to claim 1, characterized in that, The substrate of the FPC flexible circuit board is a polyimide film with a glass transition temperature ≥280℃; the thermoplastic resin is bisphenol A type polycarbonate with a Vicat softening point ≥140℃.